1991
DOI: 10.1111/j.1745-493x.1991.tb00535.x
|View full text |Cite
|
Sign up to set email alerts
|

International Purchasing Strategies of Multinational U.S. Firms

Abstract: As the global marketplace continues its relentless growth, international purchasing strategy assumes greater significance for many firms. Nevertheless, relatively few studies have reported on the general practice of purchasing professionals in international purchasing situations. This study identifies and analyzes the distinctive, dynamic, and complex aspects of international purchasing strategies prevalent among the nation's typical multinational firms. The findings should assist purchasing professionals in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 5 publications
4
94
1
Order By: Relevance
“…From these, only H1j was accepted, much in line with previous research (e.g., Birou and Fawcett, 1993;Min and Galle, 1991) who found lower cost to be a critical import motivation factor. Notably though, the variance of the dependent variable (i.e., setting imports as a corporate objective) that was explained was very weak (adjusted R 2 : .04 percent).…”
Section: [Insert Table 4 About Here]supporting
confidence: 63%
See 1 more Smart Citation
“…From these, only H1j was accepted, much in line with previous research (e.g., Birou and Fawcett, 1993;Min and Galle, 1991) who found lower cost to be a critical import motivation factor. Notably though, the variance of the dependent variable (i.e., setting imports as a corporate objective) that was explained was very weak (adjusted R 2 : .04 percent).…”
Section: [Insert Table 4 About Here]supporting
confidence: 63%
“…The above implies that the E-I dyad's attainment of competitive advantage depend on imports being a strategic objective for the importer. In addition, several studies identified lower cost as a critical factor for import motivation (e.g., Birou and Fawcett, 1993;Min and Galle, 1991 …”
Section: Importer Objectivesmentioning
confidence: 99%
“…These questions were compiled from existing literature (Carter and Vickery, 1988;Carter and Narsimhan, 1990;Min and Galle, 1991;Spekman, 1991;Birou and Fawcett, 1993;Min and Galle, 1993;Murphy and Daley, 1995). The questionnaire was pilot tested for content validity on ten organizations in India, prior to mass mailing.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the older studies cover related topics such as: purchasing volumes [7], motives for and obstacles to international procurement [7][8][9][10][11][12][13][14][15][16], supplier management [17][18][19][20], organisational issues [13,21] and the strategic integration of the procurement function [9,11,[22][23][24][25][26]. But these studies, according to Quintens [27], are often of anecdoticdescriptive nature.…”
Section: The Challenges Of Sourcing From Emerging Marketsmentioning
confidence: 99%